2006
DOI: 10.1111/j.1365-2672.2006.02965.x
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus casei metabolic potential to utilize citrate as an energy source in ripening cheese: a bioinformatics approach

Abstract: Aims:  To identify potential pathways for citrate catabolism by Lactobacillus casei under conditions similar to ripening cheese. Methods and Results:  A putative citric acid cycle (PCAC) for Lact. casei was generated utilizing the genome sequence, and metabolic flux analyses. Although it was possible to construct a unique PCAC for Lact. casei, its full functionality was unknown. Therefore, the Lact. casei PCAC was evaluated utilizing end‐product analyses of citric acid catabolism during growth in modified chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 35 publications
(66 reference statements)
1
34
1
Order By: Relevance
“…rhamnosus have been shown to convert citrate to succinate (2,33,34), while several other species of the same genus were shown not to be able to catabolize citrate (35). The conversion of citrate to succinate follows the reductive tricarboxylic acid (TCA) pathway and is typified by the presence of a transporter, termed CitT, that catalyzes the uptake of citrate in exchange with the end product suc- (27). In line with these observations, the genome of Lb.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…rhamnosus have been shown to convert citrate to succinate (2,33,34), while several other species of the same genus were shown not to be able to catabolize citrate (35). The conversion of citrate to succinate follows the reductive tricarboxylic acid (TCA) pathway and is typified by the presence of a transporter, termed CitT, that catalyzes the uptake of citrate in exchange with the end product suc- (27). In line with these observations, the genome of Lb.…”
Section: Discussionsupporting
confidence: 51%
“…No special precautions were made in the latter experiments to deplete the experimental system from residual Ca 2ϩ , and it is tentatively concluded that the Ca 2ϩ -citrate complex is the main inducing agent, which is also in line with the high affinity of the pathway for the complex. Ca 2ϩ contamination of media would explain the observed citrate consumption during growth in the absence of added Ca 2ϩ reported in previous studies (25)(26)(27). In spite of the significantly different citrate metabolic activities, growth of Lb.…”
Section: Specificity and Induction Of The Citrate Metabolic Pathway Ofmentioning
confidence: 78%
See 2 more Smart Citations
“…When NSLAB cell numbers increase, most of the residual lactose in cheese has been utilized by SLAB; therefore, NSLAB seem to better adapt to the absence of lactose in cheese than SLAB. This is dependent on their ability to utilize the substrate potentially available like milk components, bacterial metabolites, and cell lysis products (38). In a PDO long-ripened Italian cheese such as Parmigiano Reggiano, NSLAB population is mainly formed by L. paracasei, Lactobacillus rhamnosus, and Pediococcus acidilactici.…”
Section: Parmigiano Reggiano Pdomentioning
confidence: 99%